2017
DOI: 10.1536/ihj.16-656
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone-Induced Hyponatremia Masked by Tolvaptan in a Patient with an Implantable Left Ventricular Assist Device

Abstract: A 43-year-old man was referred to our hospital in June 2014 because of severe heart failure. He was diagnosed with familial dilated cardiomyopathy and was administered oral tolvaptan and amiodarone for atrial and ventricular tachycardia. Since up-titration of carvedilol had failed and he was dependent on dobutamine, a left ventricular assist device (LVAD) was implanted. Tolvaptan and furosemide were both discontinued after LVAD implantation and he was discharged from the hospital. Thirteen months later, he was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Several studies, including our data, have shown that although TLV had favorable effects, including a renoprotective effect in the acute phase of ADHF, TLV could not show any favorable long-term clinical outcomes [6,22,23]. Although several Japanese reports showed a favorable long-term effect on very limited HF patients [7,8,27], it may not be valuable in the clinical settings because these data cannot apply to all ADHF patients. In addition, recently, the guideline-based medical therapy (GDMT) for HF included sodiumglucose cotransporter (SGLT) 2 inhibitors [28] because SGLT2 inhibitors have been to have a strong clinical impact on HF [29,30].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Several studies, including our data, have shown that although TLV had favorable effects, including a renoprotective effect in the acute phase of ADHF, TLV could not show any favorable long-term clinical outcomes [6,22,23]. Although several Japanese reports showed a favorable long-term effect on very limited HF patients [7,8,27], it may not be valuable in the clinical settings because these data cannot apply to all ADHF patients. In addition, recently, the guideline-based medical therapy (GDMT) for HF included sodiumglucose cotransporter (SGLT) 2 inhibitors [28] because SGLT2 inhibitors have been to have a strong clinical impact on HF [29,30].…”
Section: Discussionmentioning
confidence: 58%
“…However, in Japan, many HF patients receive long-term TLV therapy [3], probably considering the favorable clinical response of TLV experienced by clinicians and approval when an adequate response is not obtained by other diuretics since December in Japan [24]. Recent long-term studies using TLV in Japan revealed relatively favorable TLV effects on HF patients, but in very limited patients who had many high-risk factors for rehospitalizations or who were possible TLV responders whose urine osmolality was ≥350 mOsm/L, which was a predictive marker of TLV responders [4,5,7]. Thus, in general, the long-term effect of TLV in HF patients cannot be sufficiently expected.…”
Section: Effect Of Tlv On One-year All-cause Mortality and Rehospital...mentioning
confidence: 99%
See 1 more Smart Citation
“…26 The first case report was published in 1996. 27 The mechanism by which amiodarone induces SIADH is still unclear. 28 Iovino et al suggested that amiodarone causes SIADH by stimulating anti-diuretic hormone secretion by the magnocellular neurons in the supraoptic and paraventricular nuclei of the hypothalamus or through the expression of water channel aquaporin-2 (AQP2) in the collecting ducts.…”
Section: Discussionmentioning
confidence: 99%
“… 1–4 The American Heart Association/the American College of Cardiology guideline for heart failure management suggests that the appropriate timing of beta-blocker initiation is when patients no longer require inotropes. 2 However, several real-world studies 5–7 and case reports 8–12 indicate that beta-blockers are sometimes initiated concurrently with dobutamine infusion.…”
Section: Introductionmentioning
confidence: 99%